PENGEMBANGAN BAHAN AJAR METODE DAN LATIHAN KETERAMPILAN PSIKOLOGIS PADA MATA KULIAH PSIKOLOGI OLAHRAGA - Edo, Edo Yuliandra; Utami, Rismar Julia (Dharmas Education Journal (DE_Journal), 2024)
This study aims to develop teaching materials for psychological skills methods and exercises that can be used in sports psychology courses. In sports psychology courses, psychological training theories and techniques are well-known and familiar, but their implementation in the formal sports education curriculum is still minimal. Students often only get theory without being equipped with practical guidance that can help them apply these skills in real contexts. Therefore, developing teaching materials that not only focus on theory but also involve the practice of applicable psychological skills is very important. This study is development research that uses the ADDIE model, namely analysis, design, development, implementation, and evaluation. The population and sample in this study were 60 STKIP Muhammadiyah Sungai Penuh sports education students. The results showed that students' psychological skills increased from the low category at the pretest to moderate at the posttest. The innovation of this study lies in integrating theory and practical exercises, which are expected to help students, coaches, and sports practitioners understand and train psychological skills effectively. This teaching material is expected to create an improvement in the quality of psychological skills training, which in turn will have an impact on the achievements of athletes in the future.